Efektivitas Pengelolaan Alokasi Dana Desa Pada Pemberdayaan Masyarakat Di Desa Leu Kecamatan Bolo Kabupaten Bima - Hidayatullah, Arif; Fatmawati, Fatmawati; Muhiddin, Amir (Universitas Muhammadiyah Makassar, 2022)
This study aimed to find out the Effectiveness of Village Fund Allocation Management on Community Empowerment in Leu Village, Bolo District, Bima Regency. The research method used descriptive and the instruments used in this research were observation, interviews, and documentation. The number of informants in this study were 4 people. Data analysis included data reduction, data presentation and conclusion making. The results of this study showed that the Effectiveness of Village Fund Allocation on Community Empowerment in Leu Village, Bolo District, Bima Regency. The Leu village government for the 2020 village fund budget had allocated village funds for village development programs as well as good and effective village community empowerment programs by providing business capital assistance to every micro business activist scattered throughout villages was lack business capital and also allocated. Some of the village funds were managed directly by village-owned enterprises and targeting assistance in the form of goods such as farm seeds, woven cloth to every community who really needed it.Keywords: Effectiveness, Management, Village Fund Allocation